Heat‐stress induced flowering can be a potential adaptive response to ocean warming for the iconic seagrass Posidonia oceanica. Issue 10 (17th May 2019) - Marín‐Guirao, Lazaro; Entrambasaguas, Laura; Ruiz, Juan M.; Procaccini, Gabriele
Abstract: The Mediterranean Sea is particularly vulnerable to warming and the abrupt declines experienced by the endemic Posidonia oceanica populations after recent heatwaves have forecasted severe consequences for the ecological functions and socio‐economical services this habitat forming species provides. Nevertheless, this highly clonal and long‐lived species could be more resilient to warming than commonly thought since heat‐sensitive plants massively bloomed after a simulated heatwave, which provides the species with an opportunity to adapt to climate change. Taking advantage of this unexpected plant response, we investigated for the first time the molecular and physiological mechanisms involved in seagrass flowering through the transcriptomic analysis of bloomed plants. We also aimed to identify if flowering is a stress‐induced response as suggested from the fact that heat‐sensitive but not heat‐tolerant plants flowered. The transcriptomic profiles of flowered plants showed a strong metabolic activation of sugars and hormones and indications of an active transport of these solutes within the plant, most likely to induce flower initiation in the apical meristem. Preflowered plants also activated numerous epigenetic‐related genes commonly used by plants to regulate the expression of key floral genes and stress‐tolerance genes, which could be interpreted as a mechanism to survive and optimize reproductive success under stress conditions. Furthermore, these plants provided numerous molecular clues suggesting that the factor responsible for the massive flowering of plants from cold environments (heat‐sensitive) can be considered as a stress. Heat‐stress induced flowering may thus be regarded as an ultimate response to survive extreme warming events with potential adaptive consequences for the species. Fitness implications of this unexpected stress‐response and the potential consequences on the phenotypic plasticity (acclimation) and evolutionary (adaptation) opportunity of the species to ocean warming are finally discussed.